Academic resilience of students to school engagement through perceived emotional support from the instructor, and gender variation - Lobo, Joseph; Bernardo, Bryan Dale; Alfonso, Xennell Joshua (IJERI: International Journal of Educational Research and Innovation, 2025)
Students with high academic resilience tend to cope and overcome impediments throughout the educational process. Published scholarly works have accentuated that academically resilient students are more engaged in school than their counterparts. Studies have also stressed the importance of instructor emotional support to students’ engagement in schooling. This current study is engrossed in examining academic resiliency vis-à-vis school engagement via perceived instructor emotional support from 910 samples of undergraduate students (Male: N=536, 58.9%, and Female: N=374, 41.1%) from various institutes at City College of Angeles, Philippines. Additionally, it aimed to assess the significant difference between gender concerning the three variables. Mann-Whitney U and Independent Samples T-Test were used to determine the significant difference concerning gender in academic resilience, perceived instructor emotional support, and school engagement. The findings revealed no significant difference between gender concerning school engagement, and a significant difference was found for academic resilience and perceived instructor emotional support. Partial Least Square-Structural Equation Modelling (PLS-SEM) using SmartPLS4 was performed for the mediation analysis. The findings displayed that (1) ARS is significantly related to and predicts school engagement; (2) academic resilience is positively associated with and leverages instructor emotional support; (3) perceived instructor emotional support is significantly linked to and triggers school engagement; (4) most importantly, the relationship between academic resilience and school engagement is partially mediated by perceived instructor emotional support. The results emphasized the significance of the emotional support provided by instructors in fostering resilience and engagement in undergraduate students. Findings were discoursed by highlighting the importance of promoting personal and contextual resources in the college to promote students’ overall well-being.